Maritime Cybersecurity Readiness and Training Standards in Indonesia - Rakka, Stevian G. A.; Gumilar, Bagja; Wijaya, Haryadi; Ansar, Azhar Ariansyah (Green Intelligent Systems and Applications, 2025)
The rapid digitalization of maritime operations through IoT-enabled navigation systems and cyber-physical ship infrastructures increased Indonesia’s exposure to cybersecurity risks. Strengthening cybersecurity competence within Maritime Education and Training (MET) institutions was therefore essential to ensure navigational safety, operational reliability, and national maritime resilience. This study assessed cybersecurity readiness, training standards, instructor competence, and facility availability in Indonesian MET institutions with reference to international frameworks, including IMO MSC-FAL.1/Circ.3, BIMCO guidelines, and ISO/IEC 27001. A descriptive quantitative approach was employed using structured questionnaires to evaluate organizational readiness, curriculum implementation, instructor qualifications, and supporting facilities. Data were analyzed using percentage distributions to identify institutional conditions and gaps relative to global requirements. The results indicated that cybersecurity training in most MET institutions remained largely theoretical, with limited practical exposure. Nearly 80% of respondents reported having no prior cybersecurity training, while hands-on facilities such as cyber laboratories and simulation environments were largely unavailable. Instructor expertise and standardized cybersecurity modules aligned with international guidelines were insufficient to adequately address threats to AIS, GPS, ECDIS, and integrated IT–OT systems. These findings revealed a significant gap between existing training practices and the competencies required for secure digital maritime operations. The study concluded that standardized, practice-oriented cybersecurity training was urgently needed, supported by instructor upskilling, curriculum alignment with international standards, and the development of shared training facilities. Strengthening these aspects was critical to improving national maritime cyber readiness and supporting resilient intelligent maritime systems.